Advanced organic chemistry - Carey, Francis A. (Springer, 2007)
The two-part, fifth edition of Advanced Organic Chemistry has been substantially revised and reorganized for greater clarity. The material has been updated to reflect advances in the field since the previous edition, especially in computational chemistry. Part B describes the most general and useful synthetic reactions, organized on the basis of reaction type